Anti-Proliferation Effects of Benzimidazole Derivatives on HCT-116 Colon Cancer and MCF-7 Breast Cancer Cell Lines - Al-Douh, Mohammed Hadi; Sahib, Hayder; Osman, Hasnah; Abd Hamid, Shafida; Salhimi, Salizawati M (National Cancer Center, Korea., 2012)
Benzimidazoles 1-4 were obtained using modified synthesis methods and studied for their ability to inhibit cell proliferation of colon cancer cell HCT-116 and breast cancer cell MCF-7 using MTT assays. In the HCT-116 cell line, benzimidazole 2 was found to have an IC50 value of 16.2±3.85 μg/mL and benzimidazole 1 a value of 28.5±2.91 μg/mL, while that for benzimidazole 4 was 24.08±0.31 μg/mL. In the MCF-7 cell line, benzimidazole 4 had an IC50 value of 8.86±1.10 μg/mL, benzimidazole 2 a value of 30.29±6.39 μg/mL, and benzimidazole 1 a value of 31.2±4.49 μg/mL. Benzimidazole 3 exerted no cytotoxity in either of the cell lines, with IC50 values >50 μg/mL. The results suggest that benzimidazoles derivatives may have chemotherapeutic potential for treatment of both colon and breast cancers.